Character development and youth leadership mentoring - Arshad, Mohd Mursyid; Ismail, Ismi Arif; Ahmad Fesol, Siti Feirusz; Ismail, Azman (Universiti Putra Malaysia Press, 2021)
One approach that promotes Positive Youth Development (PYD) among youth is being involved in leadership activities. Focusing on the mentoring process in a leadership development program serves as the foundation for cultivating these positive aspects for the young generation. The purpose of this study is to explore the character development process in promoting developmental assets through youth leadership mentoring. The study was conducted using qualitative research informed by the case study paradigm that involved 13 informants through in-depth interview, participant observation and document analysis as data collections. Empirical findings from the study show that mentoring process such as the display of prudent characteristics, integrity development and preferred leadership style among youth leaders lead to character development. In conclusion, the data indicated that mentoring clearly had the potential to constitute the process of character building among youth. This youth leadership mentoring process contributes to the development of their capabilities in leadership and enhances the implementation of effective youth leadership mentoring processes.